Industri Kreatif Bagi Anak Berkebutuhan Khusus di SLB 1 Payakumbuh - Eko Fikriando; Ramadhi Ramadhi; Relifra Relifra; Al Shaffaat Ronvy; Barkhia Yunas; Oza Syafriani; Yogi Fernandes (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The creative industry holds significant potential in providing economic opportunities, especially for children with special needs (CSN), who often face limitations in independently utilizing their skills after graduating from school. A community service program at SLB 1 Payakumbuh aims to empower CSN through training in creative skills, managerial reinforcement, and product marketing. Using a practice-based approach, this training includes crafting production, graphic design, and introducing digital marketing platforms. The results indicate an improvement in technical skills and self-confidence, enabling CSN to produce high-quality products with competitive market value. Nevertheless, challenges remain, particularly in accessing capital, equipment, and business network support. This program also seeks to connect CSN with local communities and business actors to foster collaborations that support the sustainability of their creative enterprises. Through entrepreneurship training, mentorship, and adequate facilities, CSN are expected to contribute independently to the creative economy while inspiring other communities to empower similar potential.